PENGEMBANGAN MEDIA GAMBAR TIGA DIMENSI POP UP DALAM PEMBELAJARAN MENULIS PUISI DI KELAS VIII SMPN 1 UJAN MAS KEPAHIANG TAHUN AJARAN 2016/2017 - Mully Cahyani Byari; Arono Arono; Gumono Gumono (Universitas Bengkulu, 2018)
This research aimed to examine and develop three-dimensional drawing media pop up in learning to writing poetry in class VIII SMP Negeri 1 Ujan Mas Kepahiang Regency Year 2016/2017. The method used in this research is research and development. The subject of this research is the class VIII A which amounts to 29 students. Technique of collecting data by observation, interview, and questionnaire. Data analysis technique is done by counting the number of percentage of the result of writing poetry. The results showed that SMPN 1 Ujan Mas needed media during the learning process, with the media can help improve students' motivation, in learning. In this research development, the researcher refers to research and development model (R & D) consisting of several steps as follows: (1) needs analysis, (2) development of three dimensional pop-up image media, (3). The percentage of students generated in writing poetry using three dimensional pop-up images is 76.96%. Based on the data analysis can be concluded the use of three-dimensional drawing media pop ups can help students in writing poetry. The learning process takes place more interesting using the three dimensional pop-up images. Keywords: learning media, pop ups, poetry